2017
DOI: 10.3389/fpsyg.2017.01882
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Effectiveness of Intergenerational Programs

Abstract: Purpose of the study: The objective of the present review study is to identify the determinant elements of the effectiveness of empirically based interventions (EBI) in the field of intergenerational work, contrasting face-to-face and combined (face-to-face and virtual) intervention modalities against variables relating to this field according to EBI indicators.Design and Methods: An extensive literature search returned a total of 553 studies. Of these, just 50 studies met the inclusion criteria of being an em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 104 publications
(36 reference statements)
1
50
0
6
Order By: Relevance
“…Another group of researchers in Spain conducted a systematic review of related literature on the topic of intergenerational experiences. They focused primarily on the effectiveness of various intergenerational programmes by evaluating empirically based interventions, which they find have scarcely been done in the intergenerational context (Canedo-García et al, 2017). While their review methodology was largely variable analysis of intergenerational programmes, part of their findings encourage development and implementation of these programmes that would meet users' needs, break down communication barriers between generations and break down social isolation of age groups (Canedo-García et al, 2017).…”
Section: Valuing the Various Ways Children Communicatementioning
confidence: 99%
“…Another group of researchers in Spain conducted a systematic review of related literature on the topic of intergenerational experiences. They focused primarily on the effectiveness of various intergenerational programmes by evaluating empirically based interventions, which they find have scarcely been done in the intergenerational context (Canedo-García et al, 2017). While their review methodology was largely variable analysis of intergenerational programmes, part of their findings encourage development and implementation of these programmes that would meet users' needs, break down communication barriers between generations and break down social isolation of age groups (Canedo-García et al, 2017).…”
Section: Valuing the Various Ways Children Communicatementioning
confidence: 99%
“…Although one of the studies detailed by Canedo-García involved a lifewriting workshop (Chippendale and Boltz, 2015), none of the interventions involved letter writing between different age groups, despite the dialogical and self-reflective nature of this social practice (Hall et al, 1999). Like the health-related programmes evaluated by Ronzi et al (2018) and Canedo-García et al (2017), letter writing has been found to be associated with 'physical and mental benefits across diverse samples' (Pennebaker andSeagal, 1999: 1252). More specifically, in a 'short [letter] writing campaign' involving 219 people, writing letters of gratitude was found to improve well-being and significantly decrease 'levels of depressive symptoms' (Toepfer et al, 2012: 198).…”
Section: Using Correspondence In Intergenerational Qualitative Researchmentioning
confidence: 99%
“…Una ilustración de ello son las publicaciones recientes a nivel internacional, punteras en el campo, Educational Psychology, y análisis de datos con técnicas rigurosas como el análisis de ítems, el análisis factorial exploratorio (AFE) y el análisis factorial confirmatorio (AFC), junto con el uso de sistemas de ecuaciones estructurales (SEM) para el análisis de validación de instrumentos (Batista, Coenders & Alonso, 2004;Cheng & Lin, 2018;Cuesta, Suárez, Lozano, García-Cueto & Muñiz, 2018;Fang, Zhang, Liu, Pan, Jin & Nie, 2017;Fuente, Cubero, Sánchez, Peralta, Garzón & Fiz, 2017;Gil, Cecato & Marí, 2018;Habok & Magyar, 2018;Lai, Zhao & Cheng, 2018;Martínez-Ferrer, Moreno & Ochoa, 2018;Milienos, Karagiannopoulou & Athanasopoulos, 2018;Nie, Teng, Zhang Pany, 2017;Oriol, Miranda, Oyanwedel & Torres, 2017;Pérez & Medrano, 2010;Peris, Maganto & Garaigordobil, 2018;Puente, Páez, Ubillos & de Costa, 2018;Rey, Mnez & Calonge, 2018;Romera, Herrera, Casas, Ortega & del Rey, 2018;Sinval, Pinto, Queirós & Maroco, 2018;Taasoobshirazi & Wang, 2016;Tian & Gao, 2018;Ventura, Barboza & Caycho, 2018;Ventura & Caycho, 2017;Ventura, Caycho, Vargas & Flóres, 2018;Widlund, Tuominen & Korhonen, 2017;Zen et al, 2019). En esta línea, se pretende avanzar en la validación de instrumentos desde las investigaciones propias desarrolladas recientemente por nosotros Canedo, García & Pacheco, 2017;García-Martín & García-Sánchez, 2013;García-Martín et al, 2014;Robledo & García, 2018).…”
Section: Tecnología De Validación De Instrumentosunclassified